A method for improving anodized pattern of highly alloyed 7000 series aluminum alloy

By adjusting the temperature and time in the thermal deformation and solution quenching treatment of 7000 series aluminum alloy, the problem of anodized spots of high alloy aluminum alloy is solved, and the effect of significantly improving the anodized spots is achieved while maintaining the alloy performance stability.

CN119194312BActive Publication Date: 2025-02-11AVIC BEIJING INST OF AERONAUTICAL MATERIALS
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411718724.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-11
Estimated Expiration
2044-11-28

AI Technical Summary

Technical Problem

The highly alloyed 7000 series aluminum alloy is prone to form anodized spots with light and dark phases after anodization, which affects the appearance and delivery.

Method used

The 7000-series aluminum alloy is heat-deformed by a relatively high thermal deformation temperature, and the relatively high solution temperature is used in the solid solution quenching treatment and a relatively long insulation time to reduce the deformation and energy storage of the alloy and regulate the dynamic and static alloy. Recovery and recrystallization behavior to avoid the formation of mixed crystal structure.

Benefits of technology

The phenomenon of anodized spots of highly alloyed 7000 series aluminum alloys has been significantly improved, the alloy performance is stable, and the operation is simple, and there is no need to improve production equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119194312B_ABST
    Figure CN119194312B_ABST
Patent Text Reader

Abstract

The present invention provides a method for improving anodized mottle of a high-alloyed 7000 series aluminum alloy. The method adopts a relatively high heat deformation temperature to perform heat deformation on the high-alloyed 7000 series aluminum alloy, and also adopts a relatively high solution temperature in combination with a relatively long holding time to perform solution quenching treatment, thereby reducing and releasing the deformation energy storage of the alloy, comprehensively regulating the dynamic, static recovery and recrystallization behaviors of the alloy, avoiding the occurrence of a mixed crystal structure of "large-size recrystallized structure + high-density subgrain structure + deformation structure", thereby achieving the purpose of significantly improving the anodized mottle of the high-alloyed 7000 series aluminum alloy without affecting the alloy properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of thermal deformation and heat treatment of 7000 series hard aluminum alloys, and relates to a method for improving anodized spots of high-alloyed 7000 series aluminum alloys. Background Art

[0002] 7000 series aluminum alloys have the advantages of light weight, high specific strength, good toughness and processing performance, and are widely used in aviation, aerospace and other fields. Weight reduction is the unchanging theme of aircraft design. Driven by this, the strength limit of this series of aluminum alloys has been continuously improved. In order to improve the strength of the alloy, its alloying degree must be improved, which makes the content of the main alloying elements Zn, Mg and Cu in this series of alloys continue to increase, resulting in Σ (Zn + Mg + Cu) usually exceeding 11.0% (mass percentage, the same below).

[0003] 7000 series aluminum alloys are mainly used to prepare primary / secondary load-bearing structural parts. Generally speaking, the preparation process is as follows: casting → homogenization → hot deformation → solution quenching → cold deformation → aging heat treatment → typical parts manufacturing → anodizing → painting → assembly. Studies have found that, unlike the relatively low-alloyed 7000 series alloys with mature applications, high-alloyed aluminum alloys with an alloying degree exceeding 11.0% will form light and dark anodized spots on the surface after anodizing, which seriously affects the appearance and delivery of typical parts. In order to improve or even eliminate this effect, it is crucial to develop a method to improve the anodized spots of high-alloyed 7000 series aluminum alloys. Summary of the invention

[0004] In order to improve the deficiencies of the prior art, the purpose of the present invention is to provide a method for improving the anodized pattern of highly alloyed 7000 series aluminum alloys, wherein the method uses a relatively high heat deformation temperature to perform thermal deformation on the highly alloyed 7000 series aluminum alloy, and also uses a relatively high solution temperature with a relatively long holding time for solution quenching treatment, thereby reducing and releasing the deformation energy storage of the alloy, comprehensively regulating the dynamic, static recovery and recrystallization behavior of the alloy, and avoiding the appearance of a mixed crystal structure of "large-size recrystallized structure + high-density subgrain structure + deformation structure", thereby achieving the purpose of significantly improving the anodized pattern of the highly alloyed 7000 series aluminum alloy without affecting the alloy properties.

[0005] The object of the present invention is achieved through the following technical solutions:

[0006] A method for improving anodized mottle of a highly alloyed 7000 series aluminum alloy, the method comprising the following steps:

[0007] 1) A high-alloyed 7000 series aluminum alloy ingot is prepared by a direct cooling semi-continuous casting method, and the high-alloyed 7000 series aluminum alloy ingot is subjected to homogenization heat treatment and machining to obtain a blank;

[0008] 2) placing the blank of step 1) into a heat preservation furnace for heat preservation treatment; wherein the temperature of the heat preservation treatment is 420-440°C, the heat preservation treatment time t1 is δ1, the unit of t1 is min, δ1 is the thickness or diameter of the minimum cross section of the blank, and the unit of δ1 is mm;

[0009] 3) performing heat deformation treatment on the blank after the heat preservation treatment in step 2) to obtain a deformed product; wherein the initial heat deformation temperature of the blank is 420-440° C., and the final heat deformation temperature of the surface of the deformed product after the heat deformation is 390-410° C.;

[0010] 4) The deformed product is subjected to solution quenching treatment. The method of solution quenching treatment is: setting the furnace temperature to (T 熔 -3)℃, and then the furnace is heated to a temperature of (T 熔 -5)℃, start timing, at (T 熔 -3)℃, keep warm for δ2×(3~4)min, quench at the right time, quenching transfer time ≤30s, quenching water temperature is 10~60℃; T 熔 is the low melting point eutectic phase peak temperature of aluminum alloy, T 熔 The unit of is ℃; δ2 is the thickness or diameter of the smallest cross section of the deformed product, and the unit of δ2 is mm;

[0011] 5) The alloy product after solution quenching in step 4) is subjected to cold deformation, aging heat treatment, machining and anodizing treatment.

[0012] According to an embodiment of the present invention, the implementation of the method can effectively improve the anodized mottle of high-alloyed 7000 series aluminum alloys. The method is simple to operate and has high compatibility. There is no need to improve the production equipment. The improvement of the anodized mottle can be achieved by using only the existing production equipment for aluminum alloy products.

[0013] According to an embodiment of the present invention, in step 1), the process parameters involved in the direct cooling semi-continuous casting method (such as casting speed, casting water flow rate, etc.) are not particularly limited, and it can be a method known in the art that can prepare highly alloyed 7000 series aluminum alloy ingots.

[0014] According to an embodiment of the present invention, in step 1), the highly alloyed 7000 series aluminum alloy refers to a 7000 series aluminum alloy having a sum of the mass percentages of the alloying elements Zn, Mg and Cu ≥ 11.0%, that is, Σ(Zn+Mg+Cu) ≥ 11.0%.

[0015] Exemplarily, the alloy composition of the high-alloyed 7000 series aluminum alloy includes ≥7.0wt% Zn; or, the alloy composition of the high-alloyed 7000 series aluminum alloy includes ≥1.2wt% Mg; or, the alloy composition of the high-alloyed 7000 series aluminum alloy includes ≥1.2wt% Cu.

[0016] According to an embodiment of the present invention, in step 1), the temperature of the homogenization heat treatment is 400°C~479°C; the time of the homogenization heat treatment is 42~60 hours. The homogenization heat treatment can be a two-stage homogenization heat treatment system or a three-stage homogenization heat treatment system; illustratively, the three-stage homogenization heat treatment system is specifically 400°C×4~6h+470°C×2~4h+475°C×36~48h; wherein, the first-stage homogenization heat treatment is mainly used to precipitate the Al3Zr phase, the second-stage homogenization heat treatment is mainly to avoid overheating of the aluminum alloy, and the third-stage homogenization heat treatment mainly plays the role of dissolving back the coarse phase. By selecting a suitable homogenization heat treatment system, it is possible to avoid the mixed crystal structure of "large-size recrystallized structure + high-density subgrained structure + deformed structure" and provide a basis for achieving the purpose of significantly improving the anodized mottle of the highly alloyed 7000 series aluminum alloy.

[0017] According to an embodiment of the present invention, in step 1), the present invention has no particular limitation on the equipment for the homogenization heat treatment, and any equipment for homogenization heat treatment well known to those skilled in the art can be used.

[0018] According to an embodiment of the present invention, in step 1), the size of the ingot is not particularly limited, and it can be an ingot for preparing a plate, an ingot for preparing a profile, or an ingot for preparing a forging; specifically, a reasonable selection can be made according to the size requirements of the final alloy product.

[0019] According to an embodiment of the present invention, in step 1), the process parameters involved in the machining are not particularly limited, and it can be a method known in the art that can transform an alloy ingot into a blank; illustratively, the machining includes removing the oxide scale on the surface of the alloy ingot and machining it to the shape required by the hot deformation treatment.

[0020] According to an embodiment of the present invention, in step 1), the size of the blank is not particularly limited, and it can be a blank for preparing a plate, a blank for preparing a profile, or a blank for preparing a forging; specifically, it can be reasonably selected according to the size requirements of the final alloy product.

[0021] According to an embodiment of the present invention, in step 2), the temperature of the heat preservation treatment is 420°C, 425°C, 430°C, 435°C or 440°C.

[0022] According to an embodiment of the present invention, in step 2), it is found that when the temperature of the insulation treatment is 420-440°C and the time t1 (in min) of the insulation treatment is the thickness or diameter δ1 (in mm) of the minimum cross-section of the blank, it can ensure that the blank is at a relatively high temperature and the temperatures of the inner and outer surfaces of the blank are consistent, which is beneficial to the reduction of deformation energy storage during thermal deformation of the alloy and provides a guarantee for reducing the formation of subgrains; it is also beneficial to the release of deformation energy storage during solution quenching, further promoting the merging of subgrain grains, strengthening the dissolution of grain boundary phases, and avoiding the formation of a mixed crystal structure of "large-size recrystallized structure + high-density subgrain structure + deformation structure", thereby avoiding the occurrence of problems such as anodizing spots due to uneven corrosion.

[0023] According to an embodiment of the present invention, in step 3), the initial heat deformation temperature is 420°C, 425°C, 430°C, 435°C or 440°C; and the final heat deformation temperature is 390°C, 395°C, 400°C, 405°C or 410°C.

[0024] According to an embodiment of the present invention, in step 3), the method of the thermal deformation treatment is not particularly limited, and the time of the thermal deformation treatment is not particularly limited, as long as the temperature before and after the thermal deformation treatment can meet the above conditions; specifically, a reasonable selection can be made according to the type of alloy product required; the thermal deformation treatment is, for example, at least one of rolling (such as hot rolling), extrusion (such as hot extrusion) or forging (such as hot forging). Exemplarily, when the required alloy product is a plate, a rolling (such as hot rolling) method can be selected for thermal deformation treatment to achieve the preparation of the plate; when the required alloy product is a profile, an extrusion (such as hot extrusion) method can be selected for thermal deformation treatment to achieve the preparation of the profile; when the required alloy product is a forging, a forging (such as hot forging) method can be selected for thermal deformation treatment to achieve the preparation of the forging.

[0025] According to an embodiment of the present invention, in step 3), it is found that when the initial thermal deformation temperature of the blank is 420-440°C and the final thermal deformation temperature of the deformed product surface after the thermal deformation is 390-410°C, that is, by controlling the temperature change range during the thermal deformation treatment to be between -10°C and -50°C (preferably -20°C and -30°C) ("-" indicates a temperature reduction), the occurrence of problems such as alloy overheating caused by too fast deformation or alloy temperature loss caused by too slow deformation during the thermal deformation treatment can be effectively prevented, which can effectively reduce the deformation energy storage of the alloy and reduce the driving force for the formation of subgrains; when further combined with subsequent solution quenching treatment, the deformation energy storage of the alloy can be further released, the merging of subgrain grains can be promoted, and the dissolution of the grain boundary phase can be strengthened, thereby avoiding the formation of high-density subgrain boundary precipitation phases caused by high-density subgrain boundaries, thereby effectively controlling the occurrence of uneven microstructures (recrystallized structure + subgrain structure + deformation structure) in the alloy and avoiding the occurrence of anodized spots.

[0026] According to an embodiment of the present invention, in step 4), the T 熔 is the low melting point eutectic phase peak temperature of the aluminum alloy, which is obtained by testing using a method known in the art; illustratively, it is obtained by testing using a DSC tester. 熔 It is 475℃~480℃, which is related to the composition of the alloy.

[0027] According to an embodiment of the present invention, in step 4), when the furnace temperature reaches (T 熔 After the temperature reaches -3)℃, the door of the holding furnace is opened and the deformed product is placed in the holding furnace for solution treatment. At this time, the temperature in the furnace will drop by more than 20℃ due to the opening of the furnace door. When the deformed product is placed in the holding furnace and the door is closed, the temperature in the furnace will rise again. When the furnace temperature rises to (T 熔 Start timing at -5)℃, keep warm for δ2×(3~4)min, and quench when the time comes.

[0028] According to an embodiment of the present invention, in step 4), a relatively high solution temperature (T 熔 -3) ℃), combined with a relatively long holding time (δ2×(3~4) min) for solution quenching treatment, on the one hand, can fully release the deformation energy storage of the alloy and promote the merging of subgrain grains; on the other hand, it can also strengthen the dissolution of the grain boundary phase, avoid the formation of high-density subgrain boundary precipitation phase caused by high-density subgrain boundaries, and avoid the appearance of recrystallized structure and deformation structure. By effectively avoiding the appearance of the mixed crystal structure of "large-size recrystallized structure + high-density subgrain structure + deformation structure", the effect of significantly improving the anodized mottle of high-alloyed 7000 series aluminum alloy is achieved.

[0029] According to an embodiment of the present invention, when the alloy ingot is a flat ingot, δ1 generally indicates the thickness of the minimum cross-section of the blank; when the alloy ingot is a round ingot, δ1 generally indicates the diameter of the blank; when the deformed product is a plate, a profile, a free forging or a die forging, δ2 generally indicates the thickness of the minimum cross-section of the deformed product; when the deformed product is a bar, δ2 generally indicates the diameter of the deformed product.

[0030] According to an embodiment of the present invention, in step 5), the cold deformation is, for example, pre-stretching or pre-compression, which can be reasonably selected according to the size and performance requirements of the desired alloy product; the pre-stretching method is not particularly limited, and it can be a pre-stretching method known in the art, and the total deformation of the pre-stretching is, for example, 1%~3%; the pre-compression method is not particularly limited, and it can be a pre-compression method known in the art, and the total deformation of the pre-compression is, for example, 1%~3%.

[0031] According to an embodiment of the present invention, in step 5), the process parameters of the aging heat treatment are not particularly defined, that is, the temperature and time of the aging heat treatment are not particularly limited, as long as the aging heat treatment of the alloy product can be achieved; illustratively, the aging heat treatment can be any one of a single-stage aging heat treatment, a two-stage aging heat treatment, or a three-stage aging heat treatment.

[0032] Exemplarily, the single-stage aging heat treatment is, for example, 120~130℃×15~25h; the double-stage aging heat treatment is, for example, 120~130℃×4~6h+152℃×18~23h; the triple-stage aging heat treatment is, for example, 120~130℃×15~25h+170~190℃×15~45min+120~130℃×15~25h.

[0033] According to an embodiment of the present invention, in step 5), the process parameters involved in the machining are not particularly limited, and alloy products with different precision and size requirements can be obtained by machining in different application sites. The specific machining method is a method known in the art that can transform a deformed product into a final alloy product; illustratively, the machining includes processing the deformed product into a part according to the drawing requirements of the final part.

[0034] According to an embodiment of the present invention, in step 5), the anodizing treatment is, for example, anodizing treatment using sulfuric acid, anodizing treatment using chromic acid, or anodizing treatment using boric acid and sulfuric acid. Exemplarily, the anodizing treatment is one of sulfuric acid anodizing treatment, chromic acid anodizing treatment, or boric acid and sulfuric acid anodizing treatment.

[0035] According to an embodiment of the present invention, in step 5), the process parameters of the sulfuric acid anodizing treatment are: sulfuric acid concentration is 150-200 g / L, oxidation time is 45-60 min, current density is 1.0-1.5 A / dm 2 , the temperature is 20~26℃.

[0036] According to an embodiment of the present invention, in step 5), the process parameters of the chromic acid anodizing treatment are: chromic acid concentration of 40-80 g / L, oxidation time of 45-60 min, oxidation voltage of 20-25 V, and temperature of 35-38 °C.

[0037] According to an embodiment of the present invention, in step 5), the process parameters of the boric acid and sulfuric acid anodizing are: sulfuric acid concentration is 30-52 g / L, boric acid concentration is 5-10 g / L, oxidation voltage is 14-16 V, temperature is 24-29° C., and oxidation time is 18-22 min.

[0038] According to the implementation mode of the present invention, the inventor of the present application has found through research that the formation mechanism of anodized spots of highly alloyed 7000 series aluminum alloys is mainly due to the morphological differences caused by uneven corrosion after anodizing treatment of uneven microstructures (recrystallized structure + subgrained structure + deformed structure) in an acidic environment. Among them, the anodized film formed by the deformed structure has the lightest color and the brightest metallic luster; the recrystallized structure is mostly manifested as relatively large-sized metallic luster stripes due to its large grain size and irregular shape, which directly reflects the morphology of the recrystallized grains; the anodized film layer formed by the subgrained structure is relatively dark and dense, especially when the high-density subgrained structure is the most obvious. Based on this, the inventor of the present application has found through research that the key to improving the anodized spots of highly alloyed 7000 series aluminum alloys is how to avoid the formation of a mixed crystal structure of "large-size recrystallized structure + high-density subgrained structure + deformed structure", thereby effectively avoiding the formation of anodized spots caused by uneven corrosion.

[0039] The present invention adopts a relatively high heat deformation temperature for heat deformation, that is, the initial heat deformation temperature of the blank is 420-440°C, and the temperature variation range during the heat deformation treatment is controlled between ~10°C and ~50°C, which can effectively reduce the deformation energy storage of the alloy and reduce the driving force for the formation of subgrains; at the same time, a relatively high solid solution temperature is used with a relatively long holding time for solid solution quenching treatment, that is, the furnace temperature is set to (T 熔 -3)℃, and then the furnace is heated to a temperature of (T 熔 -5)℃, start timing, at (T 熔The alloy is kept warm for δ2×(3~4)min at -3)℃ and then quenched. This can fully release the deformation energy storage of the alloy, promote the merging of subgrain grains, and strengthen the dissolution of grain boundary phases, avoid the formation of high-density subgrain boundary precipitation phases caused by high-density subgrain boundaries, and avoid the appearance of recrystallized and deformed structures. By effectively avoiding the appearance of the mixed crystal structure of "large-size recrystallized structure + high-density subgrain structure + deformed structure", the effect of significantly improving the anodized mottle of high-alloyed 7000 series aluminum alloys is achieved.

[0040] Beneficial effects of the present invention:

[0041] The present invention provides a method for improving the anodized mottling of a high-alloyed 7000 series aluminum alloy. The method of the present invention can effectively control the dynamic and static recovery and recrystallization behaviors of the alloy, avoid the appearance of a mixed crystal characteristic organizational structure of "recrystallization+subgrains+deformed organization", and achieve the purpose of improving the anodized mottling of a high-alloyed 7000 series aluminum alloy without affecting other properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 The three-dimensional metallographic image and anodized appearance image of the alloy product of Example 1.

[0043] Figure 2 The three-dimensional metallographic image and anodized appearance image of the alloy product of Example 2.

[0044] Figure 3 The three-dimensional metallographic image and anodized appearance image of the alloy product of Example 3.

[0045] Figure 4 The three-dimensional metallographic image and anodized appearance image of the alloy product of Example 4.

[0046] Figure 5 The three-dimensional metallographic image and anodized appearance image of the alloy product of Example 5.

[0047] Figure 6 The three-dimensional metallographic image and anodized appearance image of the alloy product of Example 6.

[0048] Figure 7 The three-dimensional metallographic image and anodized appearance image of the alloy product of Example 7.

[0049] Figure 8 The three-dimensional metallographic image and anodized appearance image of the alloy product of Example 8.

[0050] Fig. 9 The three-dimensional metallographic image and anodized appearance image of the alloy product of Example 9.

[0051] Fig.10The three-dimensional metallographic image and anodized appearance image of the alloy product of Comparative Example 1.

[0052] Fig.11 The three-dimensional metallographic image and anodized appearance image of the alloy product of Comparative Example 2.

[0053] Fig.12 The three-dimensional metallographic image and anodized appearance image of the alloy product of Comparative Example 5 are shown.

[0054] Fig.13 The anodized appearance pictures of the alloy products of Comparative Examples 7 and 8 are as follows: (a) is the anodized appearance picture of the alloy product of Comparative Example 7; (b) is the anodized appearance picture of the alloy product of Comparative Example 8; (c) is a local picture of the anodized spots of the alloy product of Comparative Example 8.

[0055] Fig.14 This is a detailed enlarged analysis diagram of the anodized spots of the alloy product of Comparative Example 8.

[0056] Fig.15 The three-dimensional metallographic image and pattern comparison image of the alloy product of Comparative Example 8, (a) is the three-dimensional metallographic image; (b) is the pattern comparison image. DETAILED DESCRIPTION

[0057] The method of the present invention will be described in further detail below in conjunction with specific examples. It should be understood that the following examples are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.

[0058] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods; the reagents, materials, etc. used in the following examples, unless otherwise specified, can be obtained from commercial channels.

[0059] Example 1

[0060] The Al-7.6Zn-1.6Mg-1.8Cu-0.12Zr alloy ingot (Σ(Zn+Mg+Cu)=11.0%, flat ingot, δ=420mm (thickness of the smallest section), T 熔 The alloy ingot is treated as follows to avoid anodizing spots on the obtained aluminum alloy plate.

[0061]

[0062] Example 2

[0063] Other operations are the same as those in Example 1, except that:

[0064]

[0065] Example 3

[0066] Other operations are the same as those in Example 1, except that:

[0067]

[0068] Example 4

[0069] The other operations are the same as those in Example 3, except that the composition of the alloy ingot is:

[0070] Al-9.0Zn-1.6Mg-2.4Cu-0.12Zr alloy ingot (Σ(Zn+Mg+Cu)=13.0%, δ=420mm, T 熔 is 478℃).

[0071] Example 5

[0072] The Al-7.6Zn-1.6Mg-1.8Cu-0.12Zr alloy ingot (Σ(Zn+Mg+Cu)=11.0%, flat ingot, δ=420mm (thickness of the smallest section), T 熔 The alloy ingot is treated as follows to avoid anodizing spots on the obtained aluminum alloy plate.

[0073]

[0074] Example 6

[0075] The Al-7.6Zn-1.6Mg-1.8Cu-0.12Zr alloy ingot (Σ(Zn+Mg+Cu)=11.0%, round ingot, δ=180mm (diameter), T 熔 The alloy ingot is treated by the following method to avoid anodizing spots on the obtained aluminum alloy profile.

[0076]

[0077] Example 7

[0078] The other operations are the same as those in Example 3, except that after pre-stretching, the aluminum alloy plate is subjected to a single-stage aging heat treatment, specifically at 120° C.×15~25h.

[0079] Example 8

[0080] The other operations are the same as those in Example 3, except that: the machined aluminum alloy plate is subjected to chromic acid anodizing treatment, specifically: the chromic acid concentration is 60 g / L, the oxidation time is 50 min, the oxidation voltage is 23 V, and the temperature is 36°C.

[0081] Example 9

[0082] The other operations are the same as those in Example 3, except that: the machined aluminum alloy plate is subjected to boric acid anodizing treatment, specifically: the sulfuric acid concentration is 42 g / L, the boric acid concentration is 8 g / L, the oxidation voltage is 15 V, the temperature is 25° C., and the oxidation time is 20 min.

[0083] Comparative Example 1

[0084] Other operations are the same as those in Example 3, except that: the initial thermal deformation temperature of the blank during the thermal deformation treatment is 400°C, and the final thermal deformation temperature of the deformed product surface after the thermal deformation is 370°C; that is, the temperature is reduced by 30°C during the thermal deformation treatment; specifically, the hot rolling process is: initial rolling temperature 400°C, process temperature drop 30°C, and final rolling temperature 370°C.

[0085] Comparative Example 2

[0086] Other operations are the same as those in Example 3, except that: the initial thermal deformation temperature of the blank during the thermal deformation treatment is 450°C, and the final thermal deformation temperature of the deformed product surface after the thermal deformation is 420°C; that is, the temperature is reduced by 30°C during the thermal deformation treatment; specifically, the hot rolling process is: initial rolling temperature 450°C, process temperature drop 30°C, and final rolling temperature 420°C.

[0087] Comparative Example 3

[0088] Other operations are the same as those in Example 3, except that: the initial thermal deformation temperature of the blank during the thermal deformation treatment is 450°C, and the final thermal deformation temperature of the deformed product surface after the thermal deformation is 390°C; that is, the temperature is reduced by 60°C during the thermal deformation treatment; specifically, the hot rolling process is: initial rolling temperature 450°C, process temperature drop 60°C, and final rolling temperature 390°C.

[0089] Comparative Example 4

[0090] Other operations are the same as those in Example 3, except that: the initial thermal deformation temperature of the blank during the thermal deformation treatment is 440°C, and the final thermal deformation temperature of the deformed product surface after the thermal deformation is 380°C; that is, the temperature is reduced by 60°C during the thermal deformation treatment; specifically, the hot rolling process is: initial rolling temperature 440°C, process temperature drop 60°C, and final rolling temperature 380°C.

[0091] Comparative Example 5

[0092] The other operations are the same as those in Example 3, except that the solution time is 150 min.

[0093] Comparative Example 6

[0094] The other operations are the same as those in Example 3, except that the solution temperature is 465°C.

[0095] Comparative Example 7

[0096] An Al-6.6Zn-1.1Mg-1.3Cu-0.12Zr alloy ingot (Σ(Zn+Mg+Cu)=9.0%, flat ingot, δ=420mm (thickness of the minimum cross-section)) was prepared by a direct cooling semi-continuous casting method, and the alloy ingot was subjected to homogenization heat treatment, hot rolling, solution quenching treatment, pre-stretching, two-stage aging heat treatment and sulfuric acid anodizing treatment by methods known in the art to finally obtain an aluminum alloy sheet.

[0097] Comparative Example 8

[0098] The other operations are the same as those of Comparative Example 7, except that the composition of the alloy ingot is:

[0099] Al-7.6Zn-1.6Mg-1.8Cu-0.12Zr alloy ingot (Σ(Zn+Mg+Cu)=11.0%).

[0100] Test Example 1

[0101] The anodized appearance, electrical conductivity, and single-point fatigue life performance of the alloy products prepared in the above embodiments and comparative examples were tested by methods known in the art, and the three-dimensional metallographic structure of the alloy products was observed. The test results are shown in Tables 1 and Figure 1 to Figure 15 shown.

[0102] Table 1 Performance test results of aluminum alloy products of embodiments and comparative examples

[0103]

[0104] It can be seen from the performance test results of Examples 1 to 9 that by adjusting the thermal deformation temperature and the solution quenching system, the deformation energy storage of the alloy can be effectively reduced and released, and the dynamic, static recovery and recrystallization behaviors of the alloy can be comprehensively regulated to avoid the appearance of a mixed crystal structure of "large-size recrystallized structure + high-density subgrain structure + deformation structure", thereby avoiding the formation of anodized spots without affecting the alloy performance.

[0105] From the performance test results of Example 4, it can be seen that the method is also applicable to 7000 series aluminum alloys with an alloying degree ≥ 13%, and it can also achieve the effect of avoiding the formation of anodized spots without affecting the alloy properties.

[0106] From the performance test results of Examples 5 and 6, it can be seen that the method is applicable to different types of aluminum alloy products, such as plates, forgings and profiles.

[0107] From the performance test results of Example 7, it can be seen that the method can match different aging heat treatment systems and can achieve the effect of improving the anodized mottle of high-alloyed 7000 series aluminum alloys.

[0108] From the performance test results of Examples 8 to 9, it can be seen that the method is suitable for different anodizing treatment methods. When different anodizing treatment methods are used, no anodizing mottle appears. This also shows that the method can significantly improve the anodizing mottle of high-alloyed 7000 series aluminum alloys.

[0109] It can be seen from the performance test results of Examples 1 to 9 that the method can not only avoid the occurrence of anodizing spots, but also the fatigue life of the obtained aluminum alloy products at 290 MPa is about 40,000 to 50,000 times, reaching a level comparable to the prior art.

[0110] It can be seen from the performance test results of Example 3 and Comparative Examples 1 to 4 that when the heat deformation temperature is adjusted outside the scope of the present application, a mixed crystal structure of "large-size recrystallized structure + high-density subgrain structure + deformation structure" will appear in the obtained alloy product, which causes a large number of spots to appear in the alloy product and the grain boundaries to coarsen. In severe cases, the fatigue performance of the alloy product will be reduced to a level of about 20,000 times.

[0111] It can be seen from the performance test results of Example 3 and Comparative Examples 5 to 6 that when the solution quenching system is adjusted outside the scope of the present application, for example, the solution time is insufficient or the solution temperature is not high, the deformation energy storage release is insufficient, and a mixed crystal structure of "large-size recrystallized structure + high-density subgrain structure + deformation structure" is exhibited, and the grain boundary phase is not fully dissolved, the mottle is significant, and the fatigue performance is also reduced to a level of about 20,000 times.

[0112] From the performance test results of Example 3 and Comparative Examples 7 to 8, it can be seen that when the degree of alloying is relatively low (Comparative Example 7), on the one hand, the element segregation on the grain boundary is not obvious, so that the difference between the grain boundaries of recrystallization, subgrains, and deformed structures after anodizing corrosion is not significant to the naked eye; on the other hand, the energy storage inside the material during thermal deformation is limited, and the energy can be fully released during solution quenching, so the resulting organizational differences are not as obvious as those of high-alloy alloys. However, when the degree of alloying is increased (Comparative Example 8), when the same process is used to produce aluminum alloy sheets, due to the significant increase in the energy storage inside the alloy material, it is very easy to form a mixed crystal organizational structure of "large-scale recrystallization + high-density subgrains + deformed structures", and the organizational differences will be significantly amplified, which will be more obvious after anodizing corrosion, as shown in the following example. Figure 13~Figure 15 shown.

[0113] From the above analysis, it can be seen that the alloy product prepared by the method of the present invention can achieve the purpose of improving anodizing spots without affecting the electrical conductivity and single-point fatigue life performance, and the improvement effect is significant.

[0114] The above is an explanation of the embodiments of the present invention. However, the present invention is not limited to the above embodiments. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for improving the anodized pattern of a highly alloyed 7000 series aluminum alloy, the method comprising the following steps: 1) A high-alloyed 7000 series aluminum alloy ingot is prepared by a direct cooling semi-continuous casting method, and the high-alloyed 7000 series aluminum alloy ingot is subjected to homogenization heat treatment and machining to obtain a blank; 2) placing the blank from step 1) into a heat preservation furnace for heat preservation treatment; wherein, The temperature of the heat preservation treatment is 420-440°C, the time t1 of the heat preservation treatment is δ1, the unit of t1 is min, δ1 is the thickness or diameter of the minimum cross section of the blank, and the unit of δ1 is mm; 3) performing heat deformation treatment on the blank after the heat preservation treatment in step 2) to obtain a deformed product; wherein the initial heat deformation temperature of the blank is 420-440° C., and the final heat deformation temperature of the surface of the deformed product after the heat deformation is 390-410° C.; 4) The deformed product is subjected to solution quenching treatment. The method of solution quenching treatment is: setting the furnace temperature to (T 熔 -3)℃, and then the furnace is heated to a temperature of (T 熔 -5)℃, start timing, at (T 熔 -3)℃, keep warm for δ2×(3~4)min, quench at the right time, quenching transfer time ≤30s, quenching water temperature is 10~60℃; T 熔 is the low melting point eutectic phase peak temperature of aluminum alloy, T 熔 The unit of is ℃; δ2 is the thickness or diameter of the smallest cross section of the deformed product, and the unit of δ2 is mm; 5) performing cold deformation, aging heat treatment, machining and anodizing treatment on the alloy product after solution quenching in step 4); The highly alloyed 7000 series aluminum alloy refers to an alloy in which the sum of the mass percentages of the alloy elements Zn, Mg and Cu is ≥ 11.0%, that is, Σ(Zn+Mg+Cu) ≥ 11.0%.

2. The method according to claim 1, wherein: The alloy composition of the highly alloyed 7000 series aluminum alloy includes ≥7.0wt% Zn; or, the alloy composition of the highly alloyed 7000 series aluminum alloy includes ≥1.2wt% Mg; or, the alloy composition of the highly alloyed 7000 series aluminum alloy includes ≥1.2wt% Cu.

3. The method according to claim 1, wherein: In step 1), the temperature of the homogenization heat treatment is 400° C. to 479° C.; and the time of the homogenization heat treatment is 42 to 60 hours.

4. The method according to claim 1, wherein: In step 3), the thermal deformation treatment is at least one of rolling, extrusion or forging.

5. The method according to claim 1, wherein: In step 5), the cold deformation is pre-stretching or pre-compression, and the total deformation of the pre-stretching is 1% to 3%; the total deformation of the pre-compression is 1% to 3%.

6. The method according to claim 1, wherein: In step 5), the aging heat treatment is any one of single-stage aging heat treatment, double-stage aging heat treatment or triple-stage aging heat treatment.

7. The method according to claim 6, wherein: The single-stage aging heat treatment is 120~130℃×15~25h; the double-stage aging heat treatment is 120~130℃×4~6h+152℃×18~23h; the triple-stage aging heat treatment is 120~130℃×15~25h+170~190℃×15~45min+120~130℃×15~25h.

8. The method according to claim 1, wherein: In step 5), the anodizing treatment is one of sulfuric acid anodizing treatment, chromic acid anodizing treatment or boric acid anodizing treatment.

9. The method according to claim 8, wherein: The process parameters of the sulfuric acid anodizing treatment are: sulfuric acid concentration of 150-200 g / L, oxidation time of 45-60 min, current density of 1.0-1.5 A / dm 2 , the temperature is 20~26℃; The process parameters of the chromic acid anodizing treatment are: chromic acid concentration of 40-80 g / L, oxidation time of 45-60 min, oxidation voltage of 20-25 V, and temperature of 35-38 ° C. The process parameters of the boric acid and sulfuric acid anodizing treatment are as follows: sulfuric acid concentration is 30-52 g / L, boric acid concentration is 5-10 g / L, oxidation voltage is 14-16 V, temperature is 24-29° C., and oxidation time is 18-22 min.

Citation Information

Patent Citations

  • Profile extrusion production process for improving anodic oxidation effect of 7075 aluminum alloy

    CN116550782A

  • Anodic oxidation 7xxx series aluminum alloy thick plate and preparation method thereof

    CN117737529A